2016
DOI: 10.2174/1381612822666160527113501
|View full text |Cite
|
Sign up to set email alerts
|

Difluorinated Curcumin: A Promising Curcumin Analogue with Improved Anti-Tumor Activity and Pharmacokinetic Profile

Abstract: This review presents an overview of the findings on metabolism and pharmacological activities of CDF, and also highlights potential opportunities to use this novel curcumin analogue in the treatment of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 151 publications
(63 citation statements)
references
References 0 publications
0
63
0
Order By: Relevance
“…It is applied in Ayurvedic medicine for treatment of inflammatory diseases for a long time. This plant and its bioactive polyphenols, curcuminoids, have been shown to exert several therapeutic actions including anti-asthmatic, 34 antioxidant, [181][182][183] immunomodulatory, 35 hepatoprotective, 36,37 antitumor, 38,40,41 and anti-inflammatory 39,184,185 activities.…”
Section: Curcuma Longamentioning
confidence: 99%
“…It is applied in Ayurvedic medicine for treatment of inflammatory diseases for a long time. This plant and its bioactive polyphenols, curcuminoids, have been shown to exert several therapeutic actions including anti-asthmatic, 34 antioxidant, [181][182][183] immunomodulatory, 35 hepatoprotective, 36,37 antitumor, 38,40,41 and anti-inflammatory 39,184,185 activities.…”
Section: Curcuma Longamentioning
confidence: 99%
“…Unlike usual curcumin, new technologies are planned to deliver therapeutic agents especially to tumors and improve anti-cancerous effects, thus avoiding systemic and unpleasant effects. 93,94 Besides, most of the point of views above were dated from in vitro and limited in vivo research including some clinical trials. There is a long way to go before curcumin can be utilized in clinical cancer treatment strategy.…”
Section: Questions and Prospectsmentioning
confidence: 99%
“…It has been identified that curcumin has a low intestinal absorption and quick metabolism in the liver and excessive excretion in the feces. Consequently, low‐water solubility and extensive first‐pass intestinal and liver metabolism leads to the low oral bioavailability of curcumin and limit its pharmacological effects (Abbas Momtazi & Sahebkar, ). Various delivery systems have been developed to enhance water solubility and systemic bioavailability of curcumin.…”
Section: Introductionmentioning
confidence: 99%